Tindak Tutur Ilokusi Penjual Pakaian Dalam Wanita Saat Live Di Tiktok Shop - Harini, Harini; Husnan, Lalu Erwan (Jurnal Pekommas, 2024)
An illocutionary speech act is an utterance uttered by the speaker with a specific purpose. This research aims to identify the illocutionary speech acts of women's underwear sellers when live on TikTok Shop and to recapitulate what illocutionary speech acts are uttered by women's underwear sellers when live on TikTok Shop and their functions. The method used in this research is qualitative. The research data is the sentences that women's underwear sellers spoken during live on TikTok Shop. The data source comes from live video recordings of women's underwear sellers on TikTok Shop. The research data was analyzed using J.R. Searle’s speech act theory. The research results show that assertive, directive, commissive, expressive, and declarative speech acts were found in the speech of women's underwear sellers while live on TikTok Shop. Of all the speech acts, the most frequently used is assertive speech acts, followed by directive and commissive speech acts.